(untitled) (Journal of Nepal Geological Society, 2003)
Middle Miocene to early Pleistocene sedimentary sequence deposited in the foreland basin of the Himalaya is represented by the Siwalik Group. In the present study area the Siwalik Group extends in a NW-SE direction and well-exposed. Fortyfour sandstone samples were studied for texture, fabric and composition in order to assess their petrographic properties and variation trends of these properties in stratigraphic levels. Sandstones were classified into sublitharenite, subarkose, lithic arenite, arkosic arenite and feldspathic graywacke and further thirteen sub-clans. Mean grain size (M) and Trask sorting coefficient (So) increase up-section. Recalculated quartz, matrix, modified maturity index (MMI), total cement (Ct), cement versus matrix index (CMI) and ratio of strong cement over total cement ((Cfc/Cs)/Ct) also increase, whilst packing proximity (PP), packing density (PD) and consolidation factor (Pcc) decrease up-section showing distinct trends, and therefore, these properties are promising in recognizing the older sandstones from the younger ones.